Uterine Extramedullary Plasmacytoma as a Primary Manifestation of Multiple Myeloma - Codorniz, Ana; Cunha, Renato; Fernandes, Fernando; Pais, Maria João; Neves, Tiago; Quintana, Carlos (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
The association between plasmacytomas and multiple myeloma (MM) is well-described, and in about one third of the cases of plasmacytoma the additional study will lead to the diagnosis of MM. The finding of plasmacytomas in the genital tract is extremely rare, with sparse cases described in the literature, and these cases pose a challenge regarding the optimal guidance and treatment. This paper describes a case of uterine extramedullary plasmacytoma in a 79-year-old woman with complaints of postmenopausal abnormal uterine bleeding. The complementary study led to the diagnosis of uterine plasmacytoma and, subsequently, of MM. Despite the unfavorable outcome of this case, we consider pertinent to report it because it constitutes a differential diagnosis to be taken into account in the approach of pelvic masses.
Keywords: plasmacytoma; multiple myeloma